2022
DOI: 10.1039/d1bm01673c
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic peptides in periodontal ligament stem cell-containing three-dimensional bioscaffolds promote bone healing

Abstract: The oligopeptide SDSSD promotes the osteogenic differentiation of human periodontal ligament stem cells. The 3D bioscaffolds with SDSSD enhance bone formation and the repair effect of bone defects in mice by regulating the AKT signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Therefore, researchers have considered using three-dimensional scaffolds to provide a more suitable environment for osteogenic differentiation of PDLSCs, enabling them to exert their osteogenic potential in other regions. Cai et al placed PDLSCs in a peptide-containing bioscaffold and observed increased bone formation while reducing chondrocyte generation ( Cai et al, 2022 ). Zhao et al co-cultured PDLSCs with umbilical vein endothelial cells (UVECs) in a calcium phosphate scaffold implanted into a cranial bone defect in a large animal model.…”
Section: Periodontal Ligament Stem Cells and Gingival Mesenchymal Ste...mentioning
confidence: 99%
“…Therefore, researchers have considered using three-dimensional scaffolds to provide a more suitable environment for osteogenic differentiation of PDLSCs, enabling them to exert their osteogenic potential in other regions. Cai et al placed PDLSCs in a peptide-containing bioscaffold and observed increased bone formation while reducing chondrocyte generation ( Cai et al, 2022 ). Zhao et al co-cultured PDLSCs with umbilical vein endothelial cells (UVECs) in a calcium phosphate scaffold implanted into a cranial bone defect in a large animal model.…”
Section: Periodontal Ligament Stem Cells and Gingival Mesenchymal Ste...mentioning
confidence: 99%
“…Among all the biologically active molecules studied in literature, oligopeptides have been proposed as an alternative to growth factors due to their high bioavailability, lower synthesis cost and easier formulation [ 150 , 151 ]. For example, Cai et al [ 150 ].…”
Section: In Vivo Advances In the 3d Bioprinting Of Bonementioning
confidence: 99%
“…Among all the biologically active molecules studied in literature, oligopeptides have been proposed as an alternative to growth factors due to their high bioavailability, lower synthesis cost and easier formulation [ 150 , 151 ]. For example, Cai et al [ 150 ]. combined the osteoblast-specific binding oligopeptide SDSSD with human periodontal ligament stem cells (PDLSCs) to develop a 3D bioscaffold and evaluated its physical and biological properties.…”
Section: In Vivo Advances In the 3d Bioprinting Of Bonementioning
confidence: 99%
“…For instance, the SDSSD peptide was immobilized on the zirconia implant surface to enhance osteoblast bioactivity [ 17 ]. Cai Mingxiang et al reported that SDSSD-modified 3D bio scaffolds facilitate osteogenesis and bone formation in the subcutaneous pocket of BALB/c nude mice and facilitate bone healing in vivo [ 18 ]. The author has also reported that bone formation was promoted by binding SDSSD to the G protein-coupled receptor and regulating the AKT signaling pathway.…”
Section: Introductionmentioning
confidence: 99%